Downtown Fresno Nuclear Freeze March to and Vigil in Courthouse Breezeway - Watkins, Howard::::::::: (1982)
??Jacqueline Pillar, Connie Petersen, Louise Erickson carrying Women's International League for Peace and Freedom banner